Individual predisposition and the intricate interplay between systemic biomarkers and periodontal risk in a general population. Issue 6 (15th January 2021) - Meisel, Peter; Nauck, Matthias; Kocher, Thomas
Abstract: Background: Increasing age is associated with systemic diseases as well as with periodontal diseases. We wondered whether a biological age score constructed exclusively from systemic biomarkers would reflect periodontal risk factors at baseline and tooth loss as well as periodontal outcome during 10 years follow‐up. Methods: From the Study of Health in Pomerania (SHIP) 2256 participants (1072 male, 1184 female) were studied for the relationship of the systemic biomarkers glycated hemoglobin (HbA1c), low density lipoprotein cholesterol (LDL), fibrinogen, white blood cell count, blood pressure, and waist circumference to their age. Construction of a biological age (BA) score allowed its comparison with the participants' actual chronological age (CA) and their predisposition to periodontal disease. Results: Though nearly identical in CA, participants appearing younger than their true age had a significantly reduced burden of periodontal risk factors. If BA > CA, then risk factors were more frequent including smoking, oral hygiene, dental visits, education, and income. After 10 years, in participants with identical CA, tooth loss followed their BA calculated at baseline, that is, with BA > CA fewer teeth were preserved. Similarly, periodontal measures varied according to BA; sex differences were obvious. Most significant were BA‐related differences in inflammatory and anthropometry parameters. Conclusions: The results support the assumption that risk profiles aggregated in BA constitute a characteristic susceptibility pattern unique to each individual, common to both systemic and periodontal diseases. Although BA was constructed exclusively from systemic measures at baseline, BA reflects the oral conditions at follow‐up.